2014
DOI: 10.1084/jem.20132477
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of microglia and monocytes in the inflamed central nervous system

Abstract: Phagocytic monocyte-derived macrophages associate with the nodes of Ranvier and initiate demyelination while microglia clear debris and display a suppressed metabolic gene signature in EAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
641
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 712 publications
(679 citation statements)
references
References 45 publications
(76 reference statements)
32
641
0
6
Order By: Relevance
“…Monocytes contribute to the inflammatory milieu in the brain just by their infiltration, even in the absence of proinflammatory cytokine induction, whereas, in microglia, the induced expression of cytokines contributes to neuroinflammation. This finding is in contrast to the antagonist response reported in EAE models (16,63). A recent study reached similar conclusions on the role of invading monocytes after SE wherein monocytes have elevated levels of TNF-α and IL-1β when normalized to control microglia (64).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Monocytes contribute to the inflammatory milieu in the brain just by their infiltration, even in the absence of proinflammatory cytokine induction, whereas, in microglia, the induced expression of cytokines contributes to neuroinflammation. This finding is in contrast to the antagonist response reported in EAE models (16,63). A recent study reached similar conclusions on the role of invading monocytes after SE wherein monocytes have elevated levels of TNF-α and IL-1β when normalized to control microglia (64).…”
Section: Discussionsupporting
confidence: 54%
“…monocytes from brain-resident microglia (16,49). Indeed, histological examination of saline solution-treated Ccr2 +/rfp animals revealed virtually no parenchymal CCR2-RFP expression in brainresident microglia (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…p21 is a p53 target gene, implicated in cell cycle arrest, tumor suppression and used as a marker of cellular senescence (Serrano et al ., 1997). Interestingly, genes previously reported in activated microglia such as Egr‐1, CCl3, Chi3l3, Chi3l4, and Lyz1 (McMahon & Monroe, 1996; Chang et al ., 2001; Babcock et al ., 2003; Friedle et al ., 2011) and in proliferation such as Fos, Jun, and Mapk8 (Yamasaki et al ., 2014) were found to be mildly but significantly downregulated in G4 mTerc −/− microglia.…”
Section: Discussionmentioning
confidence: 89%
“…Mouse microglial cells are recruited to Ab plaques (17), where they are believed to uptake plaques by phagocytosis (18,19) and release inflammatory cytokines (20), however it has been suggested that human microglia do not appear to significantly influence plaque clearance in AD brains (21). In addition to resident microglia, peripheral monocytes infiltrate the brain parenchyma under pathological condition, and several studies have indicated that infiltrating monocytes have distinct functional characteristics compared to resident microglia (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%